لطائف التذييل في سورة الحديد - القرني، عبدالهادي علي محمد آل طاهر (جامعة المنيا - كلية دار العلوم, 2022)
تدور هذه الدراسة حول بيان معنى التذييل، وأهمية دراسته، وتبرز أهمية دراسة التذييل في القرآن في وجوه، الاستعانة بهذا العلم على فهم كتاب الله، وإبراز جانب مهم من جوانب الإعجاز القرآني، الاستعانة بهذا العلم في تثبيت حفظ القرآن. وقد قدمت بتعريف التذييل لغة واصطلاحا مع بيان فوائد التذييل وأغراض، كما عرفت بالسورة الكريمة تعريفا موجزا، وذكرت مواضع التذييل التي بلغت ثمان عشر جملة. ذكرت معنى التذييل وموافقته للسياق، وبلاغته، مع بيان المعنى الإجمالي للآية التي ختمت به. ومن نتائج الدراسة أستخلص ما يلي: أغلب تذييلات السورة بأسماء الله الحسنى، بما يقرر العقيدة التي هي مقصود هذه السورة الكريمة. جاءت معظم جمل التذييل اسمية لتفيد معنى التوكيد، كما اقترنت أغلبها بمؤكدات أخرى كحرف التوكيد إن، واللام الداخلة على خبرها من جملة ٢٩ آية، بلغت جمل التذييل ١٨ جملة، بنسبة ٦٢% وهذه نسبة كبيرة مقارنة بمعظم سور القرآن الكريم. اتفقت تذييلات السورة مع مقاصدها ومعانيها، وجاءت مبينة لها ومقررة لمضامينها. This study revolves around clarifying the meaning of the appendix, and the importance of studying it. It presented the definition of the appendix linguistically and idiomatically, with an explanation of the appendix's benefits and purposes. It also briefly defined the noble surah, and mentioned the locations of the appendix, which amounted to eighteen sentences. I mentioned the meaning of the appendix and its relevance to the context, and its eloquence, with an explanation of the overall meaning of the verse that was concluded with it. From the results of the study, the following can be concluded: Most of the appendices of the surah are in the names of God, which determine the doctrine that is the purpose of this noble surah. Most of the appendix sentences were nominative to indicate the meaning of the emphasis, and most of them were associated with other affirmations, such as the emphasizing letter “inna” and the “lam” in its predicate. Out of the 29 verses, the appendix sentences amounted to 18 sentences, or 62%. This is a large percentage compared to most of the surahs of the Noble Qur’an. The appendices of the surah agreed with its purposes and meanings, and came to clarify and determine its contents.
Keywords: الإعجاز القرآني -- البلاغة القرآنية -- الألفاظ المترادفة -- الأيات القرآنية -- سورة الحديد